2022
DOI: 10.1007/s00449-022-02711-1
|View full text |Cite
|
Sign up to set email alerts
|

Lab-scale photobioreactor systems: principles, applications, and scalability

Abstract: Phototrophic microorganisms that convert carbon dioxide are being explored for their capacity to solve different environmental issues and produce bioactive compounds for human therapeutics and as food additives. Full-scale phototrophic cultivation of microalgae and cyanobacteria can be done in open ponds or closed photobioreactor systems, which have a broad range of volumes. This review focuses on laboratory-scale photobioreactors and their different designs. Illuminated microtiter plates and microfluidic devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(17 citation statements)
references
References 222 publications
0
15
0
2
Order By: Relevance
“…4a). 87 Bubble column photobioreactors ensure uniform gas supply regardless of location and usually have a cylindrical structure to allow fluid circulation. However, the systems induce shear stress on microalgae cells, which inhibits cell function and causes cell death.…”
Section: Recent Advances In Photobioreactor Systems For Microalgal Bi...mentioning
confidence: 99%
“…4a). 87 Bubble column photobioreactors ensure uniform gas supply regardless of location and usually have a cylindrical structure to allow fluid circulation. However, the systems induce shear stress on microalgae cells, which inhibits cell function and causes cell death.…”
Section: Recent Advances In Photobioreactor Systems For Microalgal Bi...mentioning
confidence: 99%
“…Intensive cultivation of microalgae is a promising method to capture and utilize the excess carbon dioxide [ 1 , 2 ]. As a result, the task of carbon footprint reduction with the simultaneous production of high-value products, theoretically, has been solved [ 3 , 4 , 5 ] and reflected in a solid number of publications [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. It was demonstrated that, depending on a variety of parameters and cultivation conditions, a high carbon fixation rate (CFR) can be achieved [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of fixed amount of CO 2 biomass and M CO2 allows for the estimatation of the efficiency of the gas-air mixture (GAM) supply and CO 2 loss. An increase in the cultivation volume to obtain a higher biomass yield leads to an increase in the CFR value, while the efficiency of CO 2 utilization decreases due to a number of challenges associated with scaling-up, ranging from energy consumption to the design of photobioreactors (PBRs) [ 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations